Synthesis and Characterization of Material LiNi0.8Co0.15Al0.05O2 Using One-Step Co-Precipitation Method for Li-Ion Batteries - Cornelius Satria Yudha; Luthfi Mufidatul Hasanah; Soraya Ulfa Muzayanha; Hendri Widiyandari; Agus Purwanto (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2019)
Li-ion battery is an energy storage device which could be applied as power source for electronic devices. The capacity of a battery is determined by the cathode material. Over this last decade, high nickel content cathode material is applied for electric vehicular technology. This study aims to synthesize a nickel-rich cathode material, LiNi0.8Co0.15Al0.05O2 (NCA) via one-step co-precipitation and study its characteristics. The Ni, Co and Al metal ion conversion during co-precipitation were analyzed using Atomic Adsorption Spectroscopy (AAS). Based on X-Ray diffraction analysis, NCA sample exhibited hexagonal-layered structure with high crystallinity. Based on Scherrer equation, the mean crystallite diameter of NCA sample is 40 nm. Scanning electron microscope (SEM) showed micron-sized homogenous particles with smooth surface. The final composition of Ni, Co and Al metal were confirmed using XRF. The capacity of the battery was determined using galvanostic test method with voltage range of 2.7-4.25 V using graphite as the counter anode. The initial specific discharge capacity of NCA is 60 mAh/g while the capacity loss per cycle is 1%.